Voices in the Urban Wilderness: Reimagining the Terms of Order in “Renaissance” Boston - Jeffrey Helgeson (Transatlantica)
Suffering both chronic decline and an acute social and economic crisis in the 1960s and 1970s, Boston’s corporate leaders began to create the initiatives that would allow the city to emerge in the succeeding decades as a leader amongst the nation’s newly thriving technology- and professional-service-based urban economies. At the same time, the city’s top-down reformers began creating new inequalities and new forms of exploitation. They also built on what has been called a “neoliberal rationality” that, in part, sought to create profit centers and market-oriented ways of living in everything from public schools, public universities, and public infrastructure to residential housing and artistic culture. This essay focuses on the work of two Bostonians in particular—writer and activist Fanny Howe and Black Power artist and activist Dana C. Chandler, Jr. (Akin Duro)—who imagined and sought to create alternative futures for Boston beginning in the late 1960s. Their work challenged not just the fact of deep inequality at the outset of an age of economic growth, but also the very terms of order that infused dominant notions of political and economic thinking. What Howe has described as “the politics of bewilderment,” or what Chandler conceived of as a people’s art of survival in response to an intrinsically violent city, provide an alternative way to approach late-twentieth-century Boston from the perspective of those who experienced it as more an urban wilderness than a renaissance city.